Mobile Application Development of Managing Elderly Household Accounts Using Speech Recognition - Nuanmeesri, Sumitra (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Using spoken language is the easiest and most natural way of communication for human beings. The communication between humans and machines using sounds or language is a huge move forward. This article demonstrates the development of a mobile application for managing household accounts with the integration of a speaking voice and touch-screen function on smartphones; this could also be used as a tool to manage household accounts for elderly Thai people. The content was evaluated by five experts to identify each feature of the developed mobile application. Afterwards, the developed mobile application was distributed to thirty-three elderly people. The findings showed that the elderly people were able to learn and use the mobile application effectively. The learning post-test results scored higher than the pre-test results. The effectiveness evaluation results in terms of the accessibility barriers that can be faced by elderly people while using mobile applications showed that the average mean was 4.13 and the standard deviation was 0.36 and the acceptance of the mobile application based on accessibility barriers that could be detected by elderly people while being used has high consensus. This indicates that the developed mobile application is effective for elderly users at a high level.